ANALISIS PELAPORAN GRI DALAM PERUSAHAAN E-COMMERCE SERTA TANTANGAN DAN POTENSI YANG DIHADAPI - Gumay, Muhammad Farrel Abigail Athallah (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
Sustainability has become a major concern in the digital economy. Stakeholders are not only focusing on the company's economic performance, but also on its social and environmental impacts. To meet these needs, e-commerce companies (Perusahaan A and Perusahaan B) publish sustainability reports with the GRI Standard to report on their activities and impacts. However, in the process, companies are faced with various challenges as well as potential that must be utilized. This study aims to understand how the disclosures made by e-commerce companies and what challenges and potentials they face. The researcher used the scoping review research method. The results of the interim analysis are that the companies have made good disclosures even though there are differences in the use of standards in one of the ESG aspects. The challenges faced by the company are potential unemployment and increased electronic waste. The potential is the efficient use of resources.